Facilitating Conditions and the Use of Plagiarism Detection Software by Postgraduates of the University of Ibadan, Oyo State, Nigeria - Jolayemi, Oluwaseun; Oyewole, Olawale; Oladejo, Oluwatosin (International Journal of Knowledge Content Development & Technology, 2024)
Plagiarism detection software is beneficial in detecting plagiarism in research works of postgraduate students. Despite the benefits of using plagiarism detection software, studies have revealed that most students, including postgraduates, do not use plagiarism detection software as expected. This could depend on the provision of facilitating conditions like internet connectivity, training opportunities and electricity. Thus, this study examined facilitating conditions and the use of plagiarism detection software among postgraduates of the University of Ibadan, Nigeria. A descriptive survey research design of the correlational type was used for this study, with a population of 2143 postgraduates. The multi-stage random sampling technique was used to determine the sample size of 242. The questionnaire was the research instrument, and data was analysed using descriptive statistics. Results showed that most postgraduates agreed that the university provided facilitating conditions like internet connectivity. The majority of the respondents noted that they used Turnitin monthly. Most of the respondents noted that they used plagiarism detection software to paraphrase their work and check the correctness of the grammar in their documents. The most prominent challenges confronting plagiarism detection software use by most respondents were their inability to afford subscription payment to use the plagiarism detection software and slow internet connectivity. There was a significant positive relationship between facilitating conditions and the use of plagiarism detection software by the postgraduates of the University of Ibadan, Nigeria. Some of the recommendations for the institution’s management include leveraging the vast network of alumni willing to give back to the institution and intervening in the provision of internet connectivity and electricity.